Embodied engagement: fostering caring thinking in a multimodal singing-based learning environment for refugee children - Mohammadhosseini, Mahsa; Schmid, Silke (Frontiers in Psychology, 2025)
Various initiatives have implemented music programs aimed at fostering refugee children’s resilience and flourishing. However, there is a lack of studies addressing the design of these educational settings with respect to the crucial role of embodiment. Hence, the challenge remains: What approaches can guide educators working with vulnerable groups? Evidence on the effects of embodied musical practices conveys a potential that resonates with fundamentals of Caring Thinking (CT) that stresses embodied, affective components. This study aims to design a Multimodal Singing-Based Learning Environment (MSLE) fostering CT among primary school-aged refugee children. Utilizing a Design-Based Research (DBR) framework, this study develops and iteratively refines the MSLE. It does so by employing the Mosaic Approach, which integrates a range of child-centered methods. Thus, the data encompass thematic drawings and videographed group activities. Focusing on the bodily dimension of children’s musical engagement, the paper explores bodily indicators of caring thinking among n = 6 7- to 10-year-old refugee children. Eight interventional workshop sessions incorporated singing in an Atelier Concept (clay sculpturing or shadow play) with a focus on symbolic expression based on the children’s affections. All sessions were videographed. Thematic analysis is used to develop patterns within the data. Initial findings suggest that integrating singing-based embodied learning practices with CT through nonverbal storytelling positively impacts children’s sense of belonging. Findings also indicate that rhythmic breathing techniques may enhance children’s regulation and relaxation responses. Singing traditional songs appears to facilitate social cohesion among participants from heterogeneous backgrounds. Additionally, group singing is associated with increased emotional expression and may attenuate symptoms of anxiety. The findings also highlight the necessity for facilitators to employ responsive pedagogical strategies to align interventions with the evolving developmental trajectories of the children. By focusing on the bodily dimension of musical engagement, the research contributes to the growing body of literature on how music education can support vulnerable populations.